Analysis of The Framing of Apostasy News in Langkat Regency via Viva.Co.Id and Antara Sumut - Ichsan, Muhammad; Deni, Indira Fatra (KURIOSITAS: Media Komunikasi Sosial dan Keagamaan, 2022)
With reference to the subject of apostasy that happened in Langkat Regency, which is presently the primary topic in two online media, namely viva.co.id and antarnews.com, this research seeks to assess the major news in the media. This study uses quantitative methods with a framing analysis model. This study uses the model of Zong Dang Pan and Gerald M. Kosicki, which divides it into four dimensions, namely: syntax, skirp, thematic, and rhetorical. The results of this study show differences in the script structure section, and there are similarities in the news content section, starting with the lead. In the script structure, the 5W elements in the two news stories have been fulfilled, but the Antaranews.com news text does not really explain the how but slightly explains the chronology related to the issue of apostasy that occurred. Meanwhile, viva.co.id explains the complete chronology of the apostasy. Both of these stories use light language in the selection of sentences within them, making it easier for readers to understand the contents of the news.